Avaliação da arquitetura da informação de bibliotecas digitais de teses e dissertações: o caso da BDTD do IBICT - Kelly Cristiane Santos Morais (2014)
This Research is an objective evaluation of the Brazilian Thesis and Dissertation Library, which concerns the Information Architecture and the Librarianship and Information Science approaches. The Literature Review was made with focus on publications about the Information Architecture and digital libraries. The Information Retrieval due to the indexing and usability of the Information Architecture was also investigated. The type of research is exploratory and applied. The Literature Review was used as a methodological approach and is a non-participant observation. The universe of this research was the Brazilian Thesis and Dissertation Library website (BDTD), maintained by the Brazilian Institute of Information Science and Technology (IBICT). The website was evaluated with a basis in a qualitative approach, as assumed by the Information Architecture. The model created by Camargo (2004), which is used in the Information Architecture for digital libraries, was employed and adapted in this work for the Data Collection. The model helped to elect the essential elements to evaluate the BDTD Information Architecture. An observation form was used as a tool to help with the structure observation and the documentation of the data collection. A critical analysis of the Information Architecture elements was possible due to the observation of how these elements approach or depart from the theoretical and methodological orientation. It was also possible to verify if an absence of the Information Architecture exists and how it impacts in the website. The results demonstrate that the Information Architecture is essential for the Digital Thesis and Dissertation Library construction/remodeling, to guarantee a rich and representative environment with good usability levels, which can help the users to easily achieve their goals. It was further observed that the Information Architecture relies on the methodologies proposed by the Librarianship and Information Science for the execution of their processes.